2014
DOI: 10.3109/2000656x.2014.964725
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the effectiveness and safety of porcine and bovine atelocollagen in Asian nasolabial fold correction

Abstract: Bovine-derived collagen has been used for soft-tissue augmentation since 1977. However, there are issues regarding the possibility of bovine spongiform encephalopathy (BSE). Researchers discovered that the histologic structure of porcine-derived collagen is similar to that of human dermal collagen and that it is free from the risk of BSE. This study was conducted to establish the effectiveness and safety of porcine-derived collagen compared to bovine-derived collagen. The 73 patients included in this study wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Another promising xenogeneic filler is bone extracellular matrix, which is 85-90% composed of type I collagen and contains multiple growth factors, also being highly permeable for therapeutic agents and cells because of fibrous network and numerous pores [17,18,[25][26][27]. Type I collagen is notable for high structure similarity between species and low immunogenicity due to its evolutionary conservativeness [28] and can also be manufactured in different dosage forms permitting its separate use where appropriate [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Another promising xenogeneic filler is bone extracellular matrix, which is 85-90% composed of type I collagen and contains multiple growth factors, also being highly permeable for therapeutic agents and cells because of fibrous network and numerous pores [17,18,[25][26][27]. Type I collagen is notable for high structure similarity between species and low immunogenicity due to its evolutionary conservativeness [28] and can also be manufactured in different dosage forms permitting its separate use where appropriate [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…At the start of its use, collagen was mainly extracted from porcine and bovine sources. Later, people started to show reticence toward this practice due to religious background, beside the proliferation of bovine spongiform encephalopathy (BSE) [ 7 ] which represented a source of hazard contamination for the extracted protein [ 8 , 9 ]. As a consequence, several researchers have been interested in marine collagen as an alternative because of the absence of disease transmission and dietary restriction [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there might be some issues regarding the possibility of transmitting animal diseases such as bovine spongiform encephalopathy. 1 Recently, it was found that nanofibers made of tilapia skin type I collagen showed good bioactivity with human keratinocytes (HaCaTs), 2 which provided the possibility of fabricating wound dressings from fish collagen. However, both pure fish collagen and mammal collagen have deficiencies of low mechanical strength and lack of antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%